PENGARUH JUMLAH UANG KARTAL, UANG GIRAL, DAN UANG KUASI TERHADAP INFLASI DI KALIMANTAN BARAT - B01109086, TAUFIK MULIANA (Jurnal Pembangunan dan Pemerataan, 2016)
This study entitled: "Effect of Amount of Money Kartal, Money Giral, And Money QuasiAgainst Inflation In West Kalimantan". The background of this research on the theory andreality to conduct research.The purpose of this study was to determine the pattern of changes in currency, demanddeposits and quasi-money against inflation in West Kalimantan and to know and analyze theinfluence of the amount of currency, demand deposits and quasi-money against inflation inWest Kalimantan to the analysis period of 2010-2014 , The data is then processed into themonthly data is then analyzed by using multiple regression analysis.Based on the results of the study as follows: 1. Kartal Money(X1) partially not have asignificant effect on inflation in West Kalimantan. 2. Giral Money (X2) partially not have asignificant effect on inflation in West Kalimantan. 3. Quasi Money (X3) partially have asignificant influence on inflation in West Kalimantan.Keywords: Kartal Money, Money Giral, Quasi Money and Inflation